Molecular Characteristics of Scylla paramamosain Ubiquitin-Conjugating Enzyme E2 and Expression Analysis During Oogenesis - Han, Kunhuang; Dai, Yanbin; Zhang, Ziping; Rao, Congwen; Zhou, Li; Wang, Yilei (Frontiers in Marine Science, 2022)
Ubiquitination is an essential post-translational modification of proteins and involved in many physiological processes, including sperm differentiation, oocyte maturation, and embryonic development. Among them, the ubiquitin-conjugating enzyme E2 plays a crucial role in gametogenesis. However, the participation of E2 in the regulation of the gonad development of crustaceans is still very limited, especially for oogenesis. In this research, we isolated and identified full-length complementary DNA of ubiquitin-conjugating enzyme E2 from mud crab (Scylla paramamosain) (Sp-Ubc2), detected distribution in different tissues by real-time quantitative PCR, and described expression patterns during oogenesis by in situ hybridization. The results demonstrated that the deduced proteins with a ubiquitin-conjugating (UBC) catalytic domain was clustered with other arthropods. In addition, the Sp-Ubc2 was widely distributed in different tissues of female individuals and kept the highest expression level in the ovary. Moreover, the expression level of Sp-Ubc2 changed significantly during oogenesis and reached peak in secondary and tertiary vitellogenesis stages. At the same time, the Sp-Ubc2 signal in the ovary gradually concentrated in nuclei. These results indicated that Sp-Ubc2 might play important roles in the cell cycle of oogenesis. This study would provide insights into the regulatory mechanism of gonad development in S. paramamosain, and it also enriched the theoretical basis of ubiquitin family genes involved in crustacean gonad development.